(3GdGbJUGO GdQjGVjs - (3YHOGdLHGQ SYjO(B, (3YaGas; (3eLjO Ydj MSjf(B, s ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2000)
(3aj gPG GdcJGH(B: (3WHjYI hfWGb GdGbJUGO GdQjGVj (B- (3GdfehPL GdGbJUGOj (B- (3JMdjd JhGRf GdShb (B- (3GdeUahaGJ hJWHjbGJgG GdGbJUGOjI (B- (3fehPL GdeSJNOe (B- (3GdefJL (B- (3GdGSYGQ aj fehPL GdeSJNOe (B- (3GdefJL (B- (3GdeTJbI hJWHjbGJgG GdGbJUGOjI (B- (3GdGeKdjI (B- (3MSGH GdJcGed hJWHjbGJg GdGbJUGOjI (B- (3eYGOdGJ GdQhb hGdfehPL GdSGcf GdebGQf hJWHjbGJgeG GdGbJUGOjI (B- (3fXQjI LGfH GdWdH (B((3fXQjI Sdhc GdeSJgdc(B) - (3JMdjd LGfH GdYQV (B)(3fXQjI GdGfJGL(B) - (3fXQjI GdJcGdja (B- (3GdHQeLI GdNWjIs
Keywords: (3GbJUGO QjGVjs